Nanocomposites with Ca and PO(4) release: Effects of reinforcement, dicalcium phosphate particle size and silanization - Xu, Hockin H. K. (2007)
OBJECTIVES: Nano-particles of dicalcium phosphate anhydrous (DCPA) were synthesized in our laboratory for the first time and incorporated into a dental resin. Our goal was to develop a mechanically strong dental composite that has Ca and PO(4) ion release to combat tooth caries, and to investigate the effects of whisker reinforcement, DCPA particle size and silanization. METHODS: DCPA nano-particles and two larger DCPA particles were used with nano-silica-fused whiskers as fillers in a resin matrix. Composite mechanical properties were measured via three-point flexure, and the release of Ca and PO(4) ions were measured vs. time. RESULTS: Using DCPA nano-particles with a diameter of 112 nm, the composite at a DCPA:whisker mass ratio of 1:1 had a flexural strength (mean ± sd; n = 5) of (112 ± 17) MPa, not significantly different from (112 ± 14) MPa of a commercial non-releasing composite; both were higher than (29 ± 7) MPa for the composite at DCPA:whisker of 1:0 (p < 0.05). The composite with DCPA particle size of 112 nm released Ca to a concentration of 0.85 mmol/L and PO(4) of 3.48 mmol/L, higher than Ca of 0.67 mmol/L and PO(4) of 1.11 mmol/L using DCPA with 12 μm particle size (p < 0.05). Silanization of DCPA increased the composite strength at DCPA:whisker of 1:0 compared to that without silanization, but decreased the Ca and PO(4) release (p < 0.05). Increasing the DCPA particle surface area increased the Ca and PO(4) release. SIGNIFICANCE: Decreasing the DCPA particle size increased the Ca and PO(4) release; whisker reinforcement increased the composite strength by 2 to 3 fold. The nano DCPA-whisker composites, with high strength and Ca and PO(4) release, may provide the needed, unique combination of stress-bearing and caries-inhibiting capabilities.